Scratch resistance enhancement of 3-glycidyloxypropyltrimethoxysilane coating incorporated with silver nanoparticles - Vengadaesvaran, B.; Arun, N.; Chanthiriga, R.; Bushroa, A.R.; Rau, S.R.; Ramesh, K.; Vikneswaran, R.; Al-Shabeeb, G.H.E.; Ramesh, S.; Arof, Abdul Kariem (Maney Publishing, 2014)
An effective method to enhance scratch resistance was developed using a 3-glycidyloxyproplytrimethoxysilane as a base on the formation of a transparent coating on glass substrate. The addition of silver nanoparticles improves further the scratch hardness of the thin film coating. The critical load obtained from the microscratch test increases from 2931 to 3319 mN upon the addition of silver nanoparticles. The size of silver nanoparticle was analysed using transmission electron microscope (TEM) and was found to be in the range of 20–40 nm. Addition of silver nanoparticles also increases the surface energy; hence the result enhances the hydrophobicity compared to substrate with only GLYMO coated on it.